Leaf Extracts of Mangifera indica L. Inhibit Quorum Sensing – Regulated Production of Virulence Factors and Biofilm in Test Bacteria - Husain, Fohad M.; Ahmad, Iqbal; Al-thubiani, Abdullah S.; Abulreesh, Hussein H.; AlHazza, Ibrahim M.; Aqil, Farrukh (Frontiers in Microbiology, 2017)
Quorum sensing (QS) is a global gene regulatory mechanism in bacteria for various traits including virulence factors. Disabling QS system with anti-infective agent is considered as a potential strategy to prevent bacterial infection. Mangifera indica L. (mango) has been shown to possess various biological activities including anti-QS. This study investigates the efficacy of leaf extracts on QS-regulated virulence factors and biofilm formation in Gram negative pathogens. Mango leaf (ML) extract was tested for quorum sensing inhibition and QS-regulated virulence factors using various indicator strains. It was further correlated with the biofilm inhibition and confirmed by electron microscopy. Phytochemical analysis was carried out using ultra performance liquid chromatography (UPLC) and GC-MS analysis. In vitro evaluation of anti-QS activity of ML extracts against Chromobacterium violaceum revealed promising dose-dependent interference in violacein production, by methanol extract. Quorum sensing inhibitory activity is also demonstrated by reduction in elastase (76%), total protease (56%), pyocyanin (89%), chitinase (55%), exopolysaccharide production (58%) and swarming motility (74%) in Pseudomonas aeruginosa PAO1 at 800 µg/ml concentration. Biofilm formation by P. aeruginosa PAO1 and Aeromonas hydrophila WAF38 was reduced considerably (36-82%) over control. The inhibition of biofilm was also observed by scanning electron microscopy. Moreover, ML extract significantly reduced mortality of C. elegans pre-infected with PAO1 at the tested concentration. Phytochemical analysis of active extracts revealed very high content of phenolics in methanol extract and a total of 14 compounds were detected by GC-MS and UPLC. These findings suggest that phytochemicals from the mango leaf could provide bioactive anti-infective and needs further investigation to isolate and uncover their therapeutic efficacy.